The Effect of Classical and Jazz Background-Music on Concentration and Reading Comprehension in Young Adult Women - Harijadi Pramono; Julia W Gunadi; Oeij A Adhika; Yenni Limyati; Herlina Gisela; Vica C Dewi (Universitas Kristen Maranatha, 2019)
Classical and jazz music activates ? brain wave that stimulate the excretion of ?-endorphins that has a role in increasing the alertness and attention. The purpose of this study was to determine the effect of classical and jazz background-music to the concentration and reading comprehension. This is a quasi experimental study, with pre-test and post-test design, performed on 30 young adult women. The measured data were Addition and reading comprehension test scores before and while listening to music. Data were analyzed using paired t-test with and non paired t-test with ?=0.05. The results showed that there were highly significant differences of Addition Test score (547.73) and reading comprehension test score (80.33) with classical music background; Addition Test score (577.47) and reading comprehension test score (78.33) with jazz music background compared to pre-treatment of classical (457.57; 61.67) (p<0.01); and jazz music (538.07; 65.00) (p<0.01) respectively. The comparison of both types of music showed no difference of Addition Test score and reading comprehension test score (p>0.05). We concluded classical and jazz background music improve concentration and reading comprehension in young adult women, with no significant differences in both types of background music. Keywords: concentration, reading comprehension, background music, classical, jazz